ANALISA FAKTOR-FAKTOR YANG PALING DOMINAN PENYEBAB KETERLAMBATAN PROYEK - Yontavinus V. Nabut; Sebastianus B. Henong; Agustinus H. Pattiraja (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2021)
The construction of construction projects in Kupang district is currently experiencing a very rapid development, many buildings and roads were built to accommodate the needs of the community. This research focuses on the factors that cause delays that occur in the construction project of the Pancasila Flobamora Monument. This research was completed using a questionnaire distributed to parties directly involved in the process of building the Flobamora monument of the Pancasila house. The results of the study found 5 factors that have the highest importance index value, namely: lack of work experience of masons (68.41%), the influence of rainy weather (66.90%), late delivery of equipment to the project location (52.36%), lack of work experience. field supervisors (43.63%), late payments by the owner (32.29%). Recommendations given are based on the delay that occurred in the construction project of the Pancasila flobamora monument, namely the lack of work experience of masons, Increasing supervision of the masons by increasing the workforce of the head of workers and foremen. The influence of rainy weather, it is better if overtime hours are applied when the weather conditions are not raining so that reduced production due to rain can be overcome, the lack of work experience of field supervisors, providing assistance and direction for less experienced field supervisors.